Monitoring System for Temperature and Humidity Sensors in the Production Room Using Node-Red as the Backend and Grafana as the Frontend - Khoirul Anam; Difa Nur Rofi; Ruci Meiyanti (Ikatan Ahli Informatika Indonesia Nusantara, 2023)
The client from the TRIAS project is facing issues with a decrease in production quality or defective products. They require a monitoring system for temperature and humidity in the production area, providing real-time notifications in case of any anomalies in temperature and humidity. However, the project has a limited budget, which poses a challenge for the contractor in developing a monitoring system that tracks temperature and humidity changes using temperature and humidity sensors as the data source. It should also provide alarms if the temperature and humidity values exceed the standard values for the room. Additionally, the pricing offer should be adjusted using information technology. The research methodology used in this study includes qualitative methods such as observation, literature review, and interviews to gather data on the mentioned issues. The SWOT method is used to analyze business process problems, while the Waterfall method is employed for system development. Based on the research findings, the researcher concludes that this project requires cost reduction in material usage and also needs a data visualization application for the mentioned sensors. The visualization application system utilizes Grafana as the frontend, chosen for its high flexibility in processing. The temperature and humidity data obtained from the sensors will be recorded by Node-Red as the backend and synchronized on the server. The data stored on the server will be saved in a MySQL database. The data from the database will be synchronized with Grafana for processing and visualization, presenting the data in easily understandable graphical forms.